A simple microfluidic platform for rapid and efficient production of the radiotracer [18F]fallypride. Issue 9 (16th April 2018) - Zhang, Xin; Liu, Fei; Knapp, Karla-Anne; Nickels, Michael L.; Manning, H. Charles; Bellan, Leon M.
Abstract : Herein, we report the development of a simple, high-throughput and efficient microfluidic system for synthesizing radioactive [ 18 F]fallypride, a PET imaging radiotracer widely used in medical research. Abstract : Herein, we report the development of a simple, high-throughput and efficient microfluidic system for synthesizing radioactive [ 18 F]fallypride, a PET imaging radiotracer widely used in medical research. The microfluidic chip contains all essential modules required for the synthesis and purification of radioactive fallypride. The radiochemical yield of the tracer is sufficient for multiple animal injections for preclinical imaging studies. To produce the on-chip concentration and purification columns, we employ a simple "trapping" mechanism by inserting rows of square pillars with predefined gaps near the outlet of microchannel. Microspheres with appropriate functionality are suspended in solution and loaded into the microchannels to form columns for radioactivity concentration and product purification. Instead of relying on complicated flow control elements ( e.g., micromechanical valves requiring complex external pneumatic actuation), external valves are utilized to control transfer of the reagents between different modules. The on-chip ion exchange column can efficiently capture [ 18 F]fluoride with negligible loss (∼98% trapping efficiency), and subsequently release a burst of concentrated [ 18 F]fluoride to the reaction cavity. A thin layer of PDMS with a small hole in the center facilitates rapid and reliable water evaporation (with the aid of azeotropic distillation and nitrogen flow) while reducing fluoride loss. During the solvent exchange and fluorination reaction, the entire chip is uniformly heated to the desired temperature using a hot plate. All aspects of the [ 18 F]fallypride synthesis were monitored by high-performance liquid chromatography (HPLC) analysis, resulting in labelling efficiency in fluorination reaction ranging from 67–87% ( n = 5). Moreover, after isolating unreacted [ 18 F]fluoride, remaining fallypride precursor, and various by-products via an on-chip purification column, the eluted [ 18 F]fallypride is radiochemically pure and of a sufficient quantity to allow for PET imaging (∼5 mCi). Finally, a positron emission tomography (PET) image of a rat brain injected with ∼300 μCi [ 18 F]fallypride produced by our microfluidic chip is provided, demonstrating the utility of the product produced by the microfluidic reactor. With a short synthesis time (∼60 min) and a highly integrated on-chip modular configuration that allows for concentration, reaction, and product purification, our microfluidic chip offers numerous exciting advantages with the potential for applications in radiochemical research and clinical production. Moreover, due to its simplicity and potential for automation, we anticipate it may be easily integrated into a clinical environment.